(untitled) (KULT_online, 2012)
Currently, the concept of ’Artistic Research’ is much discussed in the field of Cultural Studies. In this context, the anthology Vom Objekt zum Bild. Piktorale Prozesse in Kunst und Wissenschaft, 1600-2000 (From Object to Image: The Pictorial Process in Art and Science, 1600-2000) by Bettina Gockel with the assistance of Julia Häcki and Miriam Volmert examines achievements in the artistic research of still lifes. The volume illuminates the coherence of epistemology, empirical observation, and philosophical concepts as well as the visualization process of nature in artistic and scientific images. The assumption that pictures can represent epistemic categories is reviewed in ten articles exclusively dedicated to the still-life art form. The relation between these articles and scientific development is presented in detail by art historians like Werner Busch and Monika Wagner.